STUDENT NURSES’ EXPERIENCES OF CARING FOR BASIC NURSING SKILLS DURING CLINICAL PRACTICE IN RAJAWALI HOSPITAL BANDUNG - Mira Harini; Eny Kusmran (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2014)
Introduction. Clinical teaching is the means by which student nurses learn to apply the theory of nursing, facilitating integration of theoretical knowledge and practical skills in the clinical setting which becomes the art and science of nursing. Caring is values essential to professional practice and become socialized into the nursing profession. The purpose of this study was to explore nursing students’ experiences of caring for basic nursing skills during clinical practice in Rajawali hospital Bandung. Method. A qualitative research design was used and data were collected by in-depth interview. Six students from third semester who had completion of their fundamental of nursing clinical practice experience. Two instructors as key informants. Result. Analysis of collected information suggested that students do learn about caring in the clinical areas. Information analysis also revealed several common, such as feel fear and anxious, feel disgusted when helping defecation or bathing. Most students get the positive experience such as learning and respect of patients and their families. Most students were afraid to take nursing skills, poor theory-practice integration and feared looking foolish, had difficulty communicating and poor interpersonal relationships with the patients. The professional nurse challenges were to provide the best services and respect to the patients needs. Discussion. The results of the information analysis suggest some implications for nurse educators. Positive learning environments should be developed that enable students to retain clear caring values and to realize the potential of caring practice. Students require time to reflect about their clinical experience in order to integrate the experience with practicing sense of caring professional. Keywords: student nurses, caring, clinical practice